A review of antimicrobial resistance in East Africa - Lucas Ampaire; Abraham Muhindo; Patrick Orikiriza; Juliet Mwanga-Amumpaire; Lisa Bebell; Yap Boum (AOSIS, 2016)
Background and objectives: Knowledge of local and regional antimicrobial resistance (AMR) is important for clinical decision making. However, surveillance capacity for AMR is lacking throughout East Africa, and current AMR data are sparse. We sought to address this gap by summarising all available high-quality data on AMR in the East Africa region. Method: We searched the PubMed database and African Journals Online archives in April and May 2015 using the search term 'antimicrobial resistance AND sub-Saharan Africa' to find articles published from 2005 onwards. Only full-text articles in English were included. Results: We included 12 published articles in our analysis. Most articles were on bloodstream infections, hospital-based and cross-sectional in design; a majority described either community- or hospital-acquired infections. High levels of AMR to commonly-used antibiotics were reported, including 50% - 100% resistance to ampicillin and cotrimoxazole infections, emerging resistance to gentamicin (20% - 47%) and relatively high levels of resistance to ceftriaxone (46% - 69%) among Gram-negative infections. Much of the resistance was reported to be in Klebsiella species and Escherichia coli. Among Gram-positive infections, extensive resistance was reported to ampicillin (100%), gentamicin and ceftriaxone (50% - 100%), with methicillin-resistant Staphylococcus aureus prevalence ranging from 2.6% - 4.0%. Conclusion: Overall, bacterial resistance was reported among commonly-used antibiotics (ampicillin, gentamicin and ceftriaxone), raising concern that these antibiotics may no longer be useful for treating moderate or severe bacterial infections in East Africa. Thus, empirical treatment of bacterial infections needs to be reconsidered and guided by local assessment of AMR. Improvements in the limited amount of quality data and lack of harmonisation in assessing the burden of AMR are also needed.